Diseño, e implementación de un laboratorio de automatización con plcs en la Universidad Técnica de Cotopaxi sede La Maná, del cantón La Maná provincia de Cotopaxi, año 2013 - Pacheco Murillo, Carlos Anibal (2014)
The present investigation is distributed in three chapters that describe in a sequence the stages along the investigation: In the Chapter 1 Contains all the theoretical information, two similar projects were taken as reference and investigative antecedents, five main categories were taken for the development of the project, from the electric power until the programmable automata, and they were explained in the theoretical mark.